VALIDITAS DAN RELIABILITAS SKALA KEAKTIFAN BELAJAR PADA SISWA KELAS XI DI SMK PGRI 4 KEDIRI - Ayu Syafira Pramudya; Ikke Yuliani Dhian Puspitarini; Restu Dwi Ariyanto (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
Active learning is needed for every student. Because low learning activity will affect students' learning disorders. One of the things experienced by class XI students at SMK PGRI 4 Kediri in online learning is the lack of student activity in learning. This research aims to determine the validity and reliability of the learning activeness scale. active learning of students at SMK PGRI 4 Kediri class XI. Based on the results of instrument analysis using six steps in preparing the Riduwan instrument, which was adapted to the validity and reliability test using moment of product correlation and Cronbach's alpha, resulting in 41 valid statement entries with a fidelity r of 0.907, which means it is included in the high category, meaning the activity scale learning can be used by BK teachers to map the learning activities of students at SMK PGRI 4 Kediri.